Islamic law and judiciary : trend-setting judicial pronouncements on Islamic law since 1950 - Fatima, Tanzeem (New Delhi : Deep & Deep publications, 2001)
With reference to India citing various court cases.
Machine generated contents note: 1. SOURCES OF ISLAMIC LAW -- Introduction -- I. Primary Sources of Islamic Law -- 1. The Quran 2 -- 2. The Sunnat and Ahadiths (Traditions) 10 -- 3. The Ijma (Consensus of Opinion) 12 -- 4. The Qiyas (Analogical Deductions) 16 -- II. Secondary Sources of Islamic Law -- 1. Urf or Custom 18 -- 2. Judicial Decisions 20 -- 3. Legislation 20 -- 4. Justice, Equity and Good Conscience -- III. Sources of Law According to Shias -- IV. Source of Hindu Law and Islamic Law -- 2. NATURE AND CONCEPT OF MARRIAGE -- Introduction -- Origin and Concept of Marriage -- Essentials of Marriage -- Islamic Approach -- Juristic Approach -- Fact of the Case 31 -- 1. Option of Puberty: (Khyar-ul-bulugh) 39 -- 2. Restitution of Conjugal Rights 40 -- 3. Polygamy 41 -- Judicial Analysis -- Conclusion -- 3. DIVORCE -- Introduction -- Forms of Dissolutions of Marriage under -- Muslim Law -- By the Husbands 53 -- 1. Talaq-al Sunnah 53 -- 2. Talaq-ul-Biddat 55 -- 3. Ila (Vow of Continence) 55 -- 4. Zihar (Injurious Compassion) 55 -- 5. By the Wife 55 -- 6. By Mutual Consent 55 -- 7. Lian (False Charge of Adultry) 55 -- 8. False 56 -- Religious or Islamic Sanction Regarding Divorce -- An Analysis of Islamic Approach 57 -- A. Divorce by Husband 57 -- B. Divorce by Husband before Consummation 59 -- C. Divorce by Wife 60 -- D. Procedure of Divorce 61 -- Thought of Schools of Islamic Jurisprudence on -- Triple Divorce -- A. Hanafi School 67 -- B. Hambli School 68 -- C. Shafii School 68 -- Judicial Scrutiny -- Conclusion -- Suggestion -- 4. DOWER -- Introduction -- Quranic Injunctions -- Quran Ordians 83 -- Another Hadith 86 -- Definitions 87 -- Judicial Analysis -- Fact of the Case 89 -- In Case of Widow's Claim for Mahr 94 -- Conclusion -- 5. MAINTENANCE -- Introduction -- Definition of Maintenance -- Judicial Scrutiny -- Summary of the Bill of 1986 -- Conclusion -- Suggestions -- 6. PARENTAGE, LEGITIMACY AND -- ACKNOWLEDGEMENT -- A. Introduction -- 1. Parentage 141 -- 2. Legitimacy 141 -- 3. Two Methods of Legitimacy under -- Islamic Law 142 -- B. Islamic View -- 1. Minimum Period of Gestation 142 -- 2. Maximum Period of Gestation 142 -- C. Judicial Analysis -- The Evidence Act v. Pure Islamic Law 144 -- D. Conclusion -- 7. GUARDIANSHIP -- Introduction -- Definition of the Term Guardianship and -- its Classification 149 -- Guardianship 150 -- Kinds of Guardianship 151 -- Judicial Attitude 151 -- Fact of the Case 152 -- Conclusion -- 8. GIFT (HIBA) -- Introduction -- Definition 160 -- How Gifts are made-Essential Requisites 161 -- Exceptions to Gift of'Musha' 164 -- Devices against Doctrine of Musha 165 -- Judicial Trend -- Conclusion -- 9. WAKF -- Introduction of the Conception of Waqf in India -- Islamic View 171 -- Definitions, Meaning and Essentials of Waqf 172 -- Definition of Waqf under Mussalman Waqf -- Validating Act, 1913 172 -- Definition of Waqf Act, 1954 172 -- Essential of Waqf 173 -- Doctrine of Cyprus -- Application of Cyprus Doctrine 174 -- Distinction between the English and -- Islamic Law 174 -- Doctrine of Musha -- Meaning 176 -- Principle Relating to Doctrine of Musha 176 -- Judicial Trends: Wakf and the Constitutional -- Law of India 176 -- Summary of Wakf (Amendment) Act, 1984 183 -- Salient Features of the Wakf (Amendment) -- Act, 1984 189 -- New Wakf Act, 1995 191 -- Conclusion -- 10. WILL (WASIYYAT) -- Introduction -- 1. Definition and Nature of the Term Will 197 -- 2. Emergence of the Law of Will 197 -- 3. Form, Capacity and What can be Bequeathed? 198 -- Judicial Trend -- Conclusion -- 11. INHERITANCE -- Introduction -- Hanafi Law of Inheritance -- Three Classes of Heirs 206 -- 1. Sharers 206 -- 2. The Qoranic Residuaries 207 -- 3. Distant Kindred 214 -- 4. Second Kind of Distant Kindred 214 -- 5. Doctrine of Increase (Awl) 214 -- 6. Doctrine of Return (Radd) 215 -- Judicial Scrutiny -- Conclusion -- 12. APPLICATION OF TRUE ISLAMIC- -- SHARIAH LAWS: SOME SUGGESTIONS -- Annexures: -- I. The Muslim Women (Protection of Rights on -- Divorce) Act, 1986 -- II. The Wakf Act, 1954 -- III. The Wakf Act, 1995.
Includes bibliographical references (p. [374]-388) and index.
Keywords: Islamic law -- India -- Interpretation and construction